Functional imaging of COPD by CT and MRI - Lynch, David A (British journal of radiology, 2022)
This commentary reviews the contribution of imaging by CT and MRI to functional assessment in chronic obstructive pulmonary disease (COPD). CT can help individualize the assessment of COPD by quantifying emphysema, air trapping and airway wall thickening, potentially leading to more specific treatments for these distinct components of COPD. Longitudinal changes in these metrics can help assess progression or improvement. On hyperpolarized gas MRI, the apparent diffusion coefficient of provides an index of airspace enlargement reflecting emphysema. Perfusion imaging and measurement of pulmonary vascular volume on non-contrast CT provide insight into the contribution of pulmonary vascular disease to pulmonary impairment. Functional imaging is particularly valuable in detecting early lung dysfunction in subjects with inhalational exposures.